Rethinking emotional eating: Retrospective and momentary indices of emotional eating represent distinct constructs. (1st December 2021) - Chwyl, Christina; Berry, Michael P.; Manasse, Stephanie M.; Forman, Evan M.
Abstract: Emotional eating (EE) has been proposed as a key weight loss barrier. However, most investigations of EE rely on retrospective self-reports, which may have poor construct validity. This study evaluated concordance between a common self-report EE measure and a novel method for assessing momentary EE using ecological momentary assessment (EMA). We further assessed the utility of both measures for predicting both BMI and weight outcomes. Participants with overweight or obesity enrolled in a weight loss trial ( N = 163) completed a self-report measure of EE and underwent an EMA protocol that assessed momentary emotions and eating behaviors. Momentary EE was derived from EMA data using generalized linear mixed-effects models. Linear regression models examined associations between both EE measures and concurrent BMI as well as weight losses over 30 months. Retrospectively self-reported EE and momentary EE were negatively correlated with one another ( r = −0.27). Higher momentary EE and higher retrospectively reported EE both predicted higher concurrent BMI, and higher retrospectively reported EE predicted poorer weight loss outcomes at all time points ( p < 0.05). By contrast, higher momentary EE predicted improved weight outcomes at 1-year and 2-year follow-up ( p < 0.05). Our findings extend prior research suggesting that retrospective self-report EE measures capture a different construct than intended and suggest that momentary EE could predict improved weight loss outcomes.